Effects of Synbiotics, Probiotics, and Prebiotics on Liver Enzymes of Patients With Non-alcoholic Fatty Liver Disease: A Systematic Review and Network Meta-Analysis - Kanchanasurakit, Sukrit; Kositamongkol, Chayanis; Lanoi, Kamonnat; Nunta, Monnaree; Saetuan, Thaksaporn; Chaiyakunapruk, Nathorn; Saokaew, Surasak; Phisalprapa, Pochamana (Frontiers in Nutrition, 2022)
Background: A systematic review and network meta-analysis was primarily conducted to compare the effects of synbiotics, probiotics, and prebiotics on aspartate aminotransferase (AST), alanine aminotransferase (ALT). Moreover, their effects on body mass index (BMI), waist circumference (WC), lipid profile, fasting blood sugar (FBS), and homeostatic model assessment-insulin resistance (HOMA-IR) of patients with non-alcoholic fatty liver disease (NAFLD) were investigated and analyzed as secondary outcomes. Methods: The randomized controlled trials (RCTs), limited to English language, were searched through PubMed, the Web of Science, Embase, CLINAHL Plus, and the Cochrane Library from the inception to February 2, 2022. The eligible studies were reviewed and their risk-of-bias and heterogeneity were assessed. Both direct and indirect evidence were assembled using a random-effects model. The effects of the intervention were presented as weighted mean differences (WMD) with 95% confidence interval (95% CI). Results: Of 3,864 identified records, a total of 1,389 patients with NAFLD from 26 RCTs were included in the analyses. Among these, 241 were diagnosed with non-alcoholic steatohepatitis. The quality assessment reported a moderate risk of bias from most studies. Among adult patients with NAFLD, when compared with placebo, synbiotics provided the largest effect on reductions of AST (-12.71 IU/L; 95%CI: -16.95, -8.47), WC (-2.26 cm; 95% CI: -2.98, -1.54), total cholesterol (-22.23 mg/dL; 95%CI: -29.55, -14.90), low-density lipoprotein (-17.72 mg/dL; 95%CI: -25.23, -10.22), and FBS (-6.75 mg/dL; 95%CI: -10.67, -2.84). Probiotics lowered ALT (-14.46 IU/L; 95%CI: -21.33, -7.59) and triglycerides (-20.97 mg/dL; 95%CI: -40.42, -1.53) the most. None had significant impact on BMI, high-density lipoprotein, and HOMA-IR changes. Conclusion: Synbiotics and probiotics are likely to be the most potential effective treatments for AST and ALT reduction in adult patients with NAFLD, respectively. Although liver enzymes cannot exactly define the severity of NAFLD, unlike the results from biopsy or imaging tests, they are important indicators that can monitor the status of the disease and provide benefits for clinical management.